2019
DOI: 10.1007/s12325-019-01101-6
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Injection of Drugs: Literature Review of Factors Influencing Pain Sensation at the Injection Site

Abstract: The subcutaneous administration route is widely used to administer different types of drugs given its high bioavailability and rapid onset of action. However, the sensation of pain at the injection site might reduce patient adherence. Apart from a direct effect of the drug itself, several factors can influence the sensation of pain: needle features, injection site, volume injected, injection speed, osmolality, viscosity and pH of formulation, as well as the kind of excipients employed, including buffers and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
140
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(140 citation statements)
references
References 44 publications
0
140
0
Order By: Relevance
“…TNF) SC formulations containing citrate versus those without. In addition, while it has been suggested that citrate concentration might affect pain sensation, there is no clear evidence to support this statement[31]. Cohen et al…”
mentioning
confidence: 99%
“…TNF) SC formulations containing citrate versus those without. In addition, while it has been suggested that citrate concentration might affect pain sensation, there is no clear evidence to support this statement[31]. Cohen et al…”
mentioning
confidence: 99%
“…Osmolality values higher than 600 mOsm/kg has been associated to hypertonicity-induced pain. Our results showed a value lower than this limit and the pH were also at physiological range, desirable parameters in the vaccine design to avoid pain in the local injection site [42].…”
Section: Plos Onementioning
confidence: 57%
“…The administration of volumes larger than 1.5 to 2 mL usually requires multiple injections to minimize the risk of considerably high pain upon injection. For example, it has been shown that incrementing the injected volume from 0.8 to 2.25 mL resulted in an increase of the perceived pain about 1.7-fold [18,19]. The choice of the most suitable drug delivery system has to be carefully considered; the potency of the drug and the dose on the one hand and the encapsulation capacity of the delivery system on the other play a decisive role in this selection.…”
Section: Parenteral Administration Routes For Depot Injectablesmentioning
confidence: 99%
“…The choice of the most suitable drug delivery system has to be carefully considered; the potency of the drug and the dose on the one hand and the encapsulation capacity of the delivery system on the other play a decisive role in this selection. Although it has been reported that the used buffers (pH, osmolarity) in the formulations could influence the pain upon injection [18], no correlation between different lipids and the induction of pain has been investigated so far.…”
Section: Parenteral Administration Routes For Depot Injectablesmentioning
confidence: 99%